Thalassemia major patients using iron chelators showed a reduced plasma thioredoxin level and reduced thioredoxin reductase activity, despite elevated oxidative stress. (March 2015) - Ozturk, Z.; Genc, G. E.; Kupesiz, A.; Kurtoglu, E.; Gumuslu, S.
Abstract: In the present study, we aimed to investigate plasma levels of peroxiredoxin 2 (Prx2) and thioredoxin 1 (Trx1), and the activity of thioredoxin reductase (TrxR), in thalassemia major (TM) patients living in the Antalya region, Turkey. The patients were divided into three groups, according to chelators – the deferoxamine group (DFO, n = 20), the deferasirox group (DFX, n = 20), and the deferiprone group (DFP, n = 20), to compare any possible effect of chelators on antioxidative and oxidative stress parameters. A control group ( n = 20) was selected from healthy volunteers. The activities of glutathione peroxidase (GPx), glutathione reductase (GR), glutathione-S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), and TrxR, as well as the concentrations of Prx2, Trx1, glucose-6-phosphate dehydrogenase (G-6-PD), reduced glutathione (GSH), hydrogen peroxide (H2 O2 ), and malondialdehyde (MDA) were measured in the plasma samples of TM patients and the controls. The activity of CAT and the levels of H2 O2 and MDA in the TM patients were significantly higher than those in the controls, while the levels of GPx, Trx1, TrxR, and GSH were lower. The concentrations of ferritin, GSH, H2 O2, and MDA, as well as the activities of GR, CAT and TrxR, showed significant differences among the chelator groups. Although TrxR activity showed an increase in TM patients due to an elevated iron overload, both TrxR activity and Trx1 level were lower in the patient groups compared with the cases in the control group. As a result, because Trx1 level and TrxR activity were measured at a low level in the patients, increasing the levels of Trx1 and TrxR in TM patients will be a target of future treatment.